E-Government Boosts Administrative Efficiency in Rural Indonesia: E-Government Mendorong Efisiensi Administrasi di Pedesaan Indonesia - Muwardi, Alifiah Arum; Sukmana, Hendra (Indonesian Journal of Public Policy Review, 2024)
This study evaluates the effectiveness of the Plavon Dukcapil website in enhancing population administration in the Mining Village government. Using a descriptive qualitative method, the research focuses on four indicators: program target accuracy, socialization, objectives, and monitoring. Results show that while the website effectively serves its intended community, socialization efforts are lacking, leading to limited awareness among less tech-savvy residents. Despite human resource challenges, the website meets its objective of expediting administrative processes. However, formal monitoring is absent. The findings suggest a need for better socialization, continuous monitoring, and enhanced training for human resources to optimize e-government services at the village level. Highlights: Target Accuracy: Website effectively serves the community, increasing administration activities. Socialization: Limited awareness due to inadequate efforts and reliance on word of mouth. Program Monitoring: Lacks formal oversight; requires continuous monitoring and human resource training. Keywords: E-government, population administration, Mining Village, program effectiveness, qualitative study